MANAJEMEN PENGELOLAAN SAMPAH RUMAH TANGGA DI KELURAHAN KINALI KECAMTAN KAWANGKOAN - PONOMBAN, GITA; LENGKONG, FLORENCE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
Public awareness in maintaining cleanliness in the Kinali sub-district is lacking, the government has implemented a waste management procedure in Kinali Sub-District, but some people do not follow procedures that have been implemented by the government. Communities that do not follow procedures in maintaining environmental cleanliness will later have a negative impact on the health of the community and will be detrimental to the people living around the Kinali Sub-District. The purpose of this study was to determine the causes of Management of Household Waste Management in Kinali Sub-District, Kawangkoan District. This study uses descriptive qualitative research methods. Data collection techniques used are observation, interviews, and data collection with documents. To see how public awareness in maintaining cleanliness in Kinali Subdistrict, Kawangkoan District. This study uses four indicators, namely: planning, organization, mobilization, supervision. Based on the results of this study states that planning and organizing have gone well but still lack of movement and supervision from the government so that there are still people who are still littering. Thus it can be concluded that the processing up to Kinali Urban Village has not gone well.Keywords: Community, Garbage, Household